DAYA TERIMA KERUPUK GENDAR DENGAN SUBSTITUSI TEPUNG RUMPUT LAUT - fanny, Lydia; Putri, Pratiwi Eka; Kamaruddin, Hadrawaty (Media Gizi Pangan, 2020)
One of the foods that are favored by many Indonesian people is gender crackers. Gender crackers or usually also called rice crackers/puli crackers / or Karak made from rice dough mixed with herbs and flavor enhancers. To add to the nutritional value of the gender crackers, additional food ingredient is needed, that is seaweed. The benefits of seaweed are to prevent cancer, prevent strokes, prevent premature aging, maintain healthy and smooth skin, reduce blood cholesterol and blood sugar, antioxidants, and enhance immunity. The purpose of this study was to